Serotonin binding in vitro by releasable proteins from human blood platelets - Heemstra, Valerie Lawrence (Rhodes University, Faculty of Pharmacy, Pharmacy, 1984)
Among the substances released from human blood platelets are serotonin and various proteins. It was hypothesized that one of these proteins binds serotonin and that serotonin might be important to the protein's function or that the protein might be important to serotonin's function. Two platelet-specific proteins, platelet factor 4 (PF4) and ÃŸ-thromboglobulin ( ÃŸTG) were found to bind serotonin in vitro. Endogenous PF4 was isolated by serotonin-affinity chromatography and was identified by radioimmunoassay. Purified lÂ¹Â²â µ I] -PF4 and native PF4 bound to and eluted from a serotonin-affinity column similarly. Ultrafiltration of the homologous protein, (ÃŸTG, with [Â¹â ´C]-serotonin demonstrated binding of about 8 moles serotonin per mole tetrameric ÃŸTG with a dissociation con stant of about 4 x 10-8ThesisThesisâ »â ¸ M. Equilibrium dialysis of PF4 with radiolabelled serotonin was attempted, but no binding constant values were obtained because serotonin apparently bound to the dialysis membrane. Since EDTA was one of the two agents that eluted PF4 from the serotonin-affinity gel, calcium binding by -PF4 was investigated by equilibrium dialysis. Evidence was obtained for positively cooperative binding of calcium ions by PF4. It is concluded that PF4 and ÃŸTG bind serotonin in vitro, that they may also bind in vivo when platelets undergo release, and that the functions of serotonin, PF4 and ÃŸTG may be mediated in part by serotonin-protein associations.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Serotonin; Serotonin -- Metabolism